Determinants of Competitiveness of the Indian Auto Industry - Badri Narayanan G.; Pankaj Vashisht (Indian Council for Research on International Economic Relations (ICRIER), 2008)
This paper analyses the determinants of competitiveness of auto industry in India, based on a field survey and a quantitative analysis of secondary data. It highlights that all segments of Indian auto sector are growing at a fairly high rates and their productivity as well as export intensity is on the rise. Domestic sales are rising, but they have declined in certain sub-segments of vehicles. However, the R&D expenditure has been scarce. Effective rate of protection of automobile assembly is far higher than that of auto-components manufacturing. Unorganised sector, which is quite significant in auto-component manufacturing, has grown more rapidly in the urban areas than in the rural areas. The econometric analysis suggests various measures that could be taken by the government, particularly, the credit facilitation for SMEs. A field survey comprising auto manufacturers in India underlines various constraints faced by the sector, such as the shortage of skilled manpower along with poor infrastructure, fluctuating steel prices and unavailability of land at reasonable price. This suggests that the government could facilitate the industry in becoming more competitive by taking steps such as structural fiscal reforms, cut in import duties of raw materials and capital goods, promotion of R&D and FDI, training facilities, research-backed negotiations of FTAs, roadmap for harmonising emission norms across the country and infrastructure improvement. Industry, on the other hand, should improve its R&D capabilities and market research.
Keywords: L62; F14; O25; D24; 330; Indian Auto Industry; Competitiveness; Efficiency and Indian Auto Policy; Internationaler Wettbewerb; Branchenentwicklung; Institutionelle Infrastruktur; Kfz-Industrie; Indien